Eskimos in umiak, Grantley Harbor, Alaska, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: Eskimo Skin Boat, or Omiak, Grantley Harbor, Alaska. Nowell, 93 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number